High-fat diet modifies the PPAR-γ pathway leading to disruption of microbial and physiological ecosystem in murine small intestine - Duszka, Kalina (2016)
Diet is among the most important factors contributing to intestinal homeostasis, and basic functions performed by the small intestine need to be tightly preserved to maintain health. Little is known about the direct impact of high-fat (HF) diet on small-intestinal mucosal defenses and spatial distribution of the microbiota during the early phase of its administration. We observed that only 30 d after HF diet initiation, the intervillous zone of the ileum-which is usually described as free of bacteria-became occupied by a dense microbiota. In addition to affecting its spatial distribution, HF diet also drastically affected microbiota composition with a profile characterized by the expansion of Firmicutes (appearance of Erysipelotrichi), Proteobacteria (Desulfovibrionales) and Verrucomicrobia, and decrease of Bacteroidetes (family S24-7) and Candidatus arthromitus A decrease in antimicrobial peptide expression was predominantly observed in the ileum where bacterial density appeared highest. In addition, HF diet increased intestinal permeability and decreased cystic fibrosis transmembrane conductance regulator (Cftr) and the Na-K-2Cl cotransporter 1 (Nkcc1) gene and protein expressions, leading to a decrease in ileal secretion of chloride, likely responsible for massive alteration in mucus phenotype. This complex phenotype triggered by HF diet at the interface between the microbiota and the mucosal surface was reversed when the diet was switched back to standard composition or when mice were treated for 1 wk with rosiglitazone, a specific agonist of peroxisome proliferator-activated receptor-γ (PPAR-γ). Moreover, weaker expression of antimicrobial peptide-encoding genes and intervillous bacterial colonization were observed in Ppar-γ-deficient mice, highlighting the major role of lipids in modulation of mucosal immune defenses.